PATRONASE, KLIENTALISME DAN TAHTA PUTRA MAHKOTA PADA PILKADA KOTA KENDARI TAHUN 2017 - Pratama, Rekha Adji (Departemen Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2017)
One of the problems that still occur in local government bureaucracy is patronage and clientelism which is still often used by politicians to carry out a specific agenda outside the main duties and functions of the bureaucracy. This paper aims to determine the forms of patronage and clientelism that is formed in relation politicians, the bureaucrats and the community where the mayor actively